CULTURAL MEMORY AS MEMORY MANIPULATION: BETWEEN PAST EXPERIENCES AND PRESENT VALUES - Banovikj-Markovska, Angelina (МИ-АН, Центар за култура и културолошки студии, 2014)
This paper examines the culture of memory/remembrance outside national confines, i.e., seen against generational practices. As such, it stands far more vital than individual national cultures, present in the former Yugoslav space, since its symbols, icons and myths, still testify to the existence of a rather particular (unique), imaginary, multiethnic community, which though never managing to become a nation, exists, today, among people of various ethnicities, as a shared culture of memory/remembrance, in other words a specific kind of cultural memory.
Keywords: culture of memory/remembrance; generational cultural memory; social memory